New Class of Radially Adjustable Stentrievers for Acute Ischemic Stroke: Primary Results of the Multicenter TIGER Trial. Issue 5 (19th March 2021) - Gupta, Rishi; Saver, Jeffrey L.; Levy, Elad; Zaidat, Osama O.; Yavagal, Dileep; Liebeskind, David S.; Khaldi, Ahmad; Gross, Bradley; Lang, Michael; Narayanan, Sandra; Jankowitz, Brian; Snyder, Kenneth; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: The Tigertriever is a novel, radially adjustable, fully visible, stentriever that permits the operator to align radial expansion with target vessel diameters. This multicenter trial compared the Tigertriever's effectiveness and safety compared with established stent retrievers. Methods: Single arm, prospective, multicenter trial comparing the Tigertriever to efficacy and safety performance goals derived from outcomes in 6 recent pivotal studies evaluating the Solitaire and Trevo stent-retriever devices with a lead-in and a main-study phase. Patients were enrolled if they had acute ischemic stroke with National Institutes of Health Stroke Scale score ≥8 due to large vessel occlusion within 8 hours of onset. The primary efficacy end point was successful reperfusion, defined as core laboratory-adjudicated modified Thrombolysis in Cerebral Ischemia score 2b-3 within 3 passes of the Tigertriever. The primary safety end point was a composite of 90-day all-cause mortality and symptomatic intracranial hemorrhage. Secondary efficacy end points included 3-month good clinical outcome (modified Rankin Scale score 0–2) and first-pass successful reperfusion. Results: Between May 2018 and March 2020, 160 patients (43 lead-in, 117 main phase) at 17 centers were enrolled and treated with the Tigertriever. The primary efficacy end point was achieved in 84.6% in the main-study phase group compared with the 63.4% performance goal and the 73.4% historical rate (noninferiority P <0.0001; superiority P <0.01). The first pass successful reperfusion rate was 57.8%. After all interventions, successful reperfusion (modified Thrombolysis in Cerebral Ischemia score ≥2b) was achieved in 95.7% and excellent reperfusion (modified Thrombolysis in Cerebral Ischemia score 2c-3) in 71.8%. The primary safety composite end point rate of mortality and symptomatic intracranial hemorrhage was 18.1% compared with the 30.4% performance goal and the 20.4% historical rate (noninferiority P =0.004; superiority P =0.57). Good clinical outcome was achieved in 58% at 90 days. Conclusions: The Tigertriever device was shown to be highly effective and safe compared with Trevo and Solitaire devices to remove thrombus in patients with large-vessel occlusive stroke eligible for mechanical thrombectomy. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03474549.